Achieving ultrahigh anodic-efficiency and energy-density Mg–air battery via the discharge product film design of bulk Mg anode - Jialuo Huang; Zuxiang Sun; Jianxin Tan; Can Sun; Xingpeng Liao; Tao Ying; Fuyong Cao (Journal of Magnesium and Alloys, 2025)
This study exhibits a design of the discharge product film of a bulk AZ63-Ce-La-Ca (AZ63X) anode for Mg-air battery. An ideal discharge product film for Mg anode is that it could inhibit the anodic hydrogen evolution but does not hinder the transfer of the electrons at the interface. Fortunately, the addition of Ce, La, and Ca into AZ63 alloy achieves this goal. The Mg-air battery with AZ63X anode in 3.5% NaCl has an ultrahigh anodic efficiency of 85.7 ± 1.7% and energy-density of 2431 ± 53 mWh g-1 with the unique discharge product film, surpassing the values of most reported Mg-air batteries. Furthermore, the alloying elements reduce the anode delamination effect significantly by transforming the block Mg17Al12 phase into the connected Mg17Al12 structure and fine rod Al2RE and Al2Ca.